ANALISIS RASIO LIKUIDITAS SEBAGAI ALAT UKUR KINERJA KEUANGAN PADA PT GOTO GOJEK TOKOPEDIA TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Yanti Enjelika Br Hutasoit; Hendrik E.S Samosir; Mangasa Sinurat (Jurnal Akuntansi Kompetif, 2026)
This study analyzes the short-term financial performance of PT GoTo Gojek Tokopedia Tbk during 2022–2024 using liquidity ratios, including the current ratio, quick ratio, cash ratio, and net working capital. The research employs a quantitative descriptive method with secondary data from annual financial reports published by the Indonesia Stock Exchange, analyzed using horizontal analysis. The results show that the company’s liquidity performance is very strong, with all ratios consistently exceeding industry standards. However, a slight decline in liquidity ratios over the period indicates improved efficiency in utilizing current assets, particularly cash, to support operations and business expansion.